Physiotherapy Interventions in Sprain Ankle - Dewi S, Kadek S Prima; Fridayani, Ni Kadek Yuni (PT. Kesehatan Gerak Fungsi Tubuh, 2022)
Background: An ankle sprain is an injury to the joint, with a tear in the ligament due to excessive, and repetitive joint stretching. In general, sprains are caused by falls, slips, or pressure on the body that causes cartilage to cause problems in the feet. Ankle sprains occur due to muscle weakness and ligament laxity by exercising muscles and increasing LGS using exercise therapy, and can help improve muscle weakness caused by damage to the lateral ligament complex. Objective: This study aims to summarize secondary data related to sprain ankle. Methods: The research method used is a literature study using secondary data in the form of journals related to the sprain ankle topic obtained through Google Scholar, Science Direct, and PubMed. Results: Several studies have shown that someone with ankle sprains can be given physiotherapy according to their condition. Conclusion: Based on the results of the literature review, it can be said that someone who has an ankle sprain can experience pain and a decrease in LGS.